2016
DOI: 10.22235/cp.v10i2.1150
|View full text |Cite
|
Sign up to set email alerts
|

Pertenencia Social Y Comprensión De La Desigualdad Social en Niños Y Niñas De Grupos Sociales Contrastantes

Abstract: El estudio indagó las nociones sobre desigualdad social de niños y niñas de grupos sociales contrastantes, focalizando en las construcciones cognitivas infantiles considerando los contextos sociales de pertenencia. Se desarrolló un estudio cualitativo, descriptivo y transversal. Se realizaron 67 entrevistas semi-estructuradas a niños/as de 10 y 11 años de nivel socioeconómico medio-alto y bajo de la ciudad de Córdoba, seleccionados/as por muestreo teórico. Los datos fueron procesados mediante Análisis de Conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Third, since the work of Henry and Saul (2006), no studies have analyzed inequality justification in children. Exploration of this topic with children and adolescents remains a potential approach to studying subjective aspects of inequality justification, especially as Latin American studies suggest that from an early age social inequality is understood and value judgments are made around it (e.g., Acuña Figueroa et al, 2016;Imhoff & Brussino, 2015b; see also Chapter 4, this volume). In addition, research that assesses perceived social inequality would benefit from considering several dimensions of inequality (not only the economic dimension, but also legal and educational, among others), in that Latin American studies based on system justification theory have shown differential subjective dynamics depending on the dimensions of inequality considered.…”
Section: Potential Future Directions For Research and Intervention On...mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, since the work of Henry and Saul (2006), no studies have analyzed inequality justification in children. Exploration of this topic with children and adolescents remains a potential approach to studying subjective aspects of inequality justification, especially as Latin American studies suggest that from an early age social inequality is understood and value judgments are made around it (e.g., Acuña Figueroa et al, 2016;Imhoff & Brussino, 2015b; see also Chapter 4, this volume). In addition, research that assesses perceived social inequality would benefit from considering several dimensions of inequality (not only the economic dimension, but also legal and educational, among others), in that Latin American studies based on system justification theory have shown differential subjective dynamics depending on the dimensions of inequality considered.…”
Section: Potential Future Directions For Research and Intervention On...mentioning
confidence: 99%
“…In addition, in Brazil, several researchers have focused on the analysis of various aspects related to how the elites-economic, political, religious, and intellectual, among othersunderstand social inequality and poverty (Coelho de Oliveira, 2010;Reis, 2000;Scalon, 2007;Vasconcelos, 2017). There have also been some contributions to the understanding of social inequality and socioeconomic stratification among children in Argentina (e.g., Acuña Figueroa et al, 2016;Imhoff & Brussino, 2015b), Chile (e.g., del Río & Strasser, 2007;Palavecino et al, 2000), and Mexico (e.g., Díaz Barriga et al, 1992).…”
mentioning
confidence: 99%